Citizenship, Belonging and Intergenerational Relations in African Migration
XIV, 219 p.
Keywords: This book explores migration experiences of African families across two generations in Britain, France and South Africa. Global processes of African migration are investigated, and the lived experiences of African migrants are explored in areas such as citizenship, belonging, intergenerational transmission, work and social mobility.